Regieren durch Argumentieren? Macht und Legitimität politischer Sprache im Prozess der europäischen Integration - Barbato, Mariano (Regieren in Europa | Governance in Europe, 2023)
The power and legitimacy of European argumentation are in decline. Nevertheless, interests and ideas continue to count in Europe only when they are put forward as arguments. Beyond argumentation, Europe is ungovernable. Two questions are at the centre of this volume: What does argumentation mean? What are Europe's arguments? Based on Aristoteles and Wittgenstein, the first part of the book develops a method for narrating political argumentation. The second part presents the topic of historical language games from the European Coal and Steel Community to the Green New Deal. This book will appeal in equal measure to anyone with a practical interest in the EU and anyone with a linguistic, philosophical interest in political science.